The law and practice of arbitration and conciliation : the Arbitration and Conciliation Act, 1996 - Malhotra, O. P. [ (Om Prakash)] , 1923-; Malhotra, Indu (LexisNexis Butterworths, 2002)
Commentary on the Arbitration and Conciliation Act, 1996